THE REFLECTION OF THE GLOBAL CAPITALISM SYSTEM IN SUZANNE COLLINS’S THE HUNGER GAMES - Thahir, Muhammad Fadhly; Rahman, Fathu; Makka, Mustafa (JURNAL ILMU BUDAYA, 2018)
The aim of this research is to describe the reflection of the global capitalism system in Suzanne Collins’s novel The Hunger Games. This research also explains on how the influences between The Hunger Games with the portrait of the global capitalism in the world. The research uses qualitative descriptive methods trough sociology of literature theory. It focuses on the relation of intrinsic elements in the literary works with the reality aspect from the society. The data constitute both primary and supporting data. The primary data was taken from the novel itself The Hunger Games, while supporting data are taken from books, theses, journal and articles from internet which related to the topic of the research. The result of research shows that The Hunger Games novel represented the global capitalism system in many ways. The differences between Capitol and all districts considered as the symbol of capitalism system where the rich get richer and the poor get poorer. The government of Panem which stayed in Capitol can be easily to control and dictated the people across the countryside. The global capitalism system in the novel reflected through the way of government of Panem control the economic side, market value, and political side.